A knowledge, attitude and practice study on awareness and acceptance of contraceptives in postpartum women in a tertiary care hospital - Gupte, Jessica; Sane, Ishan; Junnare, Ketaki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Postpartum family planning (PPFP) is crucial to prevent unintended pregnancies and promote maternal and child health. However, postpartum contraceptive awareness and acceptance remain low in many developing countries, including India, where high fertility rates contribute to rapid population growth and strain health care resources. This study aims to assess the knowledge, attitudes, and practices (KAP) regarding contraceptives among postpartum women in a tertiary care hospital in Pune, Maharashtra. Methods: This cross-sectional study was conducted from May 2024 to August 2024 in the obstetrics and gynaecology department of a tertiary care hospital. A total of 211 postpartum women were recruited based on inclusion criteria, and a self-structured questionnaire was administered to gather data on contraceptive awareness, attitudes, and acceptance. The data was then analyzed further. Results: Of the 211 participants, 87.2% were aware of contraceptive methods, with the highest awareness of barrier contraceptives, followed by oral contraceptive pills and intrauterine devices (IUDs). Despite this high awareness, only 39.8% of the participants chose to adopt contraceptives during the postpartum period. The most accepted method was IUDs (81%), while the primary reasons for non-acceptance included the desire for more children (44.9%) and fear of infertility (21.3%). Conclusions: Although awareness of contraceptives among postpartum women in this study was high, the acceptance rate was significantly lower. Factors such as cultural beliefs, fear of infertility, and spousal refusal contribute to non-acceptance. Addressing these barriers through targeted education and counselling during the postpartum period may increase contraceptive uptake and ultimately improve maternal and child health outcomes.